2018
DOI: 10.21449/ijate.443222
|View full text |Cite
|
Sign up to set email alerts
|

Functional Status of Women and Their Partners After Childbirth

Abstract: Abstract:The aim of this study is to define the changes within the social dimension of the functional status of women and their partners in the months following the birth of their child. A total of 90 participants were included in the study (45 women and 45 partners). Data were collected in two steps via face-to-face interviews. The first step involved administration of a personal information form and the functional status inventories to the women and their partners between the postpartum sixth and eighth week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
1
2
0
2
Order By: Relevance
“…Although other studies have shown different results,59 60 the present study observed that women who gave birth with vaginal delivery were more likely to belong to the poor functional trajectory group compared with those who had a caesarean section. Similar finding was obtained in a study from Turkey that women who had a caesarean section had better functional status in the area of household activities at 6 th month of postpartum period, compared with those who gave normal birth 61. This might be due to the fact that women who had caesarean delivery may have received more family support because of their surgery than those women with vaginal delivery.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Although other studies have shown different results,59 60 the present study observed that women who gave birth with vaginal delivery were more likely to belong to the poor functional trajectory group compared with those who had a caesarean section. Similar finding was obtained in a study from Turkey that women who had a caesarean section had better functional status in the area of household activities at 6 th month of postpartum period, compared with those who gave normal birth 61. This might be due to the fact that women who had caesarean delivery may have received more family support because of their surgery than those women with vaginal delivery.…”
Section: Discussionsupporting
confidence: 85%
“…Similar finding was obtained in a study from Turkey that women who had a caesarean section had better functional status in the area of household activities at 6 th month of postpartum period, compared with those who gave normal birth. 61 This might be due to the fact that women who had caesarean delivery may have received more family support because of their surgery than those women with vaginal delivery. Another justification might be as FOC is linked to vaginal birth, 62 women who had vaginal birth might have experienced high levels of FOC, which reduces their level of self-confidence, and in turn decreases their functional status.…”
Section: Discussionmentioning
confidence: 99%
“…(2018)'nın çalışmasında ise sezaryen doğum yapan kadınların altıncı ayda DSFDE puan ortalamaları daha yüksek rapor edilmiştir. 21 Ülkemizde yapılan iki çalışmanın bulgularına göre ise doğum öncesi eğitimin (doğuma hazırlık sınıfı ve antenatal eğitim) kadınların doğum sonu fonksiyonel durumları üzerine etkisinin olmadığı saptanmıştır. 37,39 Araştırmada yaşın artmasıyla sahip olunan çocuk sayısının artması kadınlara tecrübe kazandırmış olabilir.…”
Section: Discussionunclassified
“…19,20 Doğum sonrası kadınların fonksiyonel durumu etkileyen çok sayıda faktör vardır. Kadınların demografik özellikleri (yaş, eğitim, aile şekli vb) 19 obstetrik özellikleri (gebeliği planlama ve isteme durumu vb) [19][20][21] ve psikososyal özellikleri (ev ve bebek bakımına ilişkin doğum sonu destek varlığı vb.) 20…”
Section: Doğumunclassified
“…The functional status of women after childbirth gradually decreases. The decrease in this level of functionality may come to a level that will affect both maternal health and infant care (12). Especially the decrease in sleep duration and quality can reduce the energy of mothers in the next day (13).…”
Section: Introductionmentioning
confidence: 99%